AtELP4 a subunit of the Elongator complex in Arabidopsis, mediates cell proliferation and dorsoventral polarity during leaf morphogenesis - Jun, Sang Eun; Cho, Kiu-Hyung; Manzoor, Muhammad Aamir; Hwang, Tae Young; Kim, Youn Soo; Schaffrath, Raffael; Kim, Gyung-Tae (Frontiers in Plant Science, 2022)
The Elongator complex in eukaryotes has conserved tRNA modification functions and contributes to various physiological processes such as transcriptional control, DNA replication and repair and chromatin accessibility. ARABIDOPSIS ELONGATOR PROTEIN 4 (AtELP4) is one of the six subunits (AtELP1-AtELP6) in Arabidopsis Elongator. In addition, there is an Elongator-associated protein, DEFORMED ROOTS AND LEAVES 1 (DRL1), whose homolog in yeast (Kti12) binds tRNAs. In this study, we explored the functions of AtELP4 in plant specific aspects such as leaf morphogenesis and in evolutionarily conserved ones between yeast and Arabidopsis. ELP4 comparison between yeast and Arabidopsis revealed that plant ELP4 possesses not only a highly conserved P-loop ATPase domain but also unknown plant-specific motifs. ELP4 function is partially conserved between Arabidopsis and yeast in the growth sensitivity towards caffeine and elevated cultivation temperature. Either single Atelp4 or drl1-102 mutants and double Atelp4 drl1-102 mutants exhibited a reduction in cell proliferation and changed adaxial-abaxial polarity of leaves. In addition, the single Atelp4 and double Atelp4 drl1-102 mutants showed remarkable downward curling at whole part of leaf blades in contrast to wild type leaf blades. Furthermore, our genetic study revealed AtELP4 might epistatically act on DRL1 in the regulation of cell proliferation and dorsoventral polarity in leaves. Taken together, we suggest that AtELP4 as part of the plant Elongator complex may act upstream of a regulatory pathway for adaxial-abaxial polarity and cell proliferation during leaf development.